Comparison of plantar loads during treadmill and overground running - Hong, Y.; Wang, L.; Li, J. X.; Zhou, J. H. (Journal of Science and Medicine in Sport, 2012)
Objectives: The objective of this study is to compare plantar loads during treadmill running and running on concrete and grass surfaces. Design: Crossover study design was used in the study. Methods: A total of 16 experienced heel-to-toe runners participated in the study. Plantar loads data were collected using a Novel Pedar insole sensor system during running on the treadmill, concrete, and grass surfaces at 3.8 m/s running speed and then analyzed. Results: Compared with running on the two other surfaces, treadmill running showed a lower magnitude of maximum plantar pressure and maximum plantar force for the total foot, maximum plantar pressure at two toe regions, and maximum plantar force for the medial forefoot region and two toe regions (p < 0.0017). Treadmill running also showed a longer absolute contact time at two toe regions compared with running on the other two surfaces (p < 0.0017). Conclusions: Treadmill running is associated with a lower magnitude of maximum plantar pressure and a lower maximum plantar force at the plantar areas. These results suggest that the plantar load distribution in treadmill running is not the same as the plantar load distribution in running on overground surfaces. Treadmill running may be useful in early rehabilitation programs. Patients with injuries in their lower extremities may benefit from the reduction in plantar loads. However, the translation to overground running needs investigation.